If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4 = -39 Reorder the terms: 4 + 3x = -39 Solving 4 + 3x = -39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3x = -39 + -4 Combine like terms: 4 + -4 = 0 0 + 3x = -39 + -4 3x = -39 + -4 Combine like terms: -39 + -4 = -43 3x = -43 Divide each side by '3'. x = -14.33333333 Simplifying x = -14.33333333
| 10=2(c+1)+2 | | 7(3x-2)=5(2x-1) | | 24x-3(8x-18)=54 | | 6x+2(2x-3)=24 | | 7p-6p=-11 | | Y=0.25x^2+10x+80 | | 3x^(-1/2)=8 | | 12-v=9 | | 4x+5x-34=68-8x | | 3x^(-1/2)-8=0 | | (a*a)-5a+25+(b*b)+6b+36=0 | | -6=3(x-19) | | 4x+x-15+x-4=180 | | 6-2x=6x-10x-16 | | 5b+6b-9b+1=7 | | 2(1-2a)=7(a-6) | | 2(x-3)-3=3 | | 11=4(n-17)+15 | | 7-z=-3 | | 12x+24y=60 | | ((4y^4/3x^4y^7))^3 | | 4s-3s=15 | | 8a^4=9a^2 | | 1/2:1/2 | | (a*a)-5a+25+(b*b)+6b+61=0 | | 11x+-9x-3=-9 | | G(x)=f(x+3)+1 | | (4y^4/3x^4y^7)^3 | | 11x+-9r-3=-9 | | c+x^2+40x=0 | | 13+x=y-17 | | -20x+5y=15 |